2022
DOI: 10.1615/critreveukaryotgeneexpr.2021039235
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA FOXD2-AS1 Promotes Pancreas Adenocarcinoma Cell Invasion and Migration by Sponging miR-30a-3p to Upregulate COX-2

Abstract: Introduction: FOXD2-AS1 is known to promote the development of several cancers. However, its role in pancreatic adenocarcinoma (PAAD) is unclear.Methods: Expression of FOXD2-AS1 and miR-30a-3p in PAAD patients was analyzed with RT-qPCR. A follow-up study was performed to analyze the prognostic value of FOXD2-AS1 for PAAD. Overexpression assays were performed to analyze the crosstalk between FOXD2-AS1 and miR-30a-3p. Cell invasion and migration were analyzed by transwell assays.Results: Analysis of the TCGA dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Multiple reports have shown that FOXD2-AS1 plays an important role in the development of multiple tumors, including the promotion of malignant progression of bile duct cancer via regulation of the miR-760/E2F3 axis ( Hu et al, 2022 ). FOXD2-AS1 may promote pancreatic cancer cell invasion and migration by sponging miR-30a-3p, which upregulates COX-2 ( Ye et al, 2022 ). FOXD2-AS1 promotes breast cancer cell proliferation, invasion, migration, and drug resistance by positively regulating the PI3K/AKT signaling pathway, inhibits apoptosis, and accelerates breast cancer progression ( Nong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports have shown that FOXD2-AS1 plays an important role in the development of multiple tumors, including the promotion of malignant progression of bile duct cancer via regulation of the miR-760/E2F3 axis ( Hu et al, 2022 ). FOXD2-AS1 may promote pancreatic cancer cell invasion and migration by sponging miR-30a-3p, which upregulates COX-2 ( Ye et al, 2022 ). FOXD2-AS1 promotes breast cancer cell proliferation, invasion, migration, and drug resistance by positively regulating the PI3K/AKT signaling pathway, inhibits apoptosis, and accelerates breast cancer progression ( Nong et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total number of 179 tumors along with 171 normal tissues were included in the analysis. The association of ASF1B expression level with the overall survival of PDAC patients was analyzed using Kaplan–Meier Plotter in GEPIA online resources, with a total of 178 cases being included (Ye et al 2022 ). Four databases including Starbase ( https://starbase.sysu.edu.cn/starbase2/index.php ), Targetscan ( http://www.targetscan.org/vert_71/ ), miRDB ( http://mirdb.org/ ) and miRWalk ( http://mirwalk.umm.uni-heidelberg.de/ ) were employed to predict the miRNAs with possible binding sites with ASF1B mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, the transcription of the entire eukaryotic genome will produce countless non-protein RNA species, and non-coding RNA (ncRNAs) is one of non-protein RNA species. 1 Studies showed that 80% of the DNA is transcribed into RNA but only a meager 1.5% of that RNA actually translates into protein. 2 Initially, ncRNAs were once considered as "evolutionary junk" lacking the potential to code protein.…”
Section: Introductionmentioning
confidence: 99%